Hubungan Pola Asuh Demokratis Orang Tua dengan Kemampuan Pengambilan Keputusan Karir Siswa - Yurike Kinanthy Karamoy (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2018)
This study aims to determine the relationship between parents’ democratic parenting and students’ career decision-making ability at SMAN 3 Jember. This quantitative descriptive correlational research sampled 100 students out of 152 population of class XII student at SMAN 3 Jember using proportionate random sampling technique. From the results of the descriptive analysis, the average level of students’ career decision-making ability is included in the high category with a percentage of 70.94% and the average level of parents’ democratic parenting is included in the good category of 76.08%. The results of the correlation statistical analysis obtained the correlation coefficient r = 0.481 (r> 0.195) with a significance of p = 0.000 (p <0.05). The discussion in this study was directed to find out the applications of parents’ democratic parenting with career decision-making abilitiy in class XII of SMAN 3 Jember. Keywords: democratic parenting, career decision-making ability